2021
DOI: 10.3390/min11040416
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending the Causes of Presence of Copper and Common Heavy Metals in Sediments of Irrigation Canals in Taiwan

Abstract: In 2019, Taiwan completed its first thorough heavy metal investigation of irrigation canal sediments by this study with the support of Taiwan Environmental Protection Administration. Box-and-whisker plots were used to analyze the sediment distribution and to define metal concentrations. Possible metal pollution sources, the polluted agricultural land, irrigation area, and water sources were also evaluated using spatial analysis to understand the possible causes of sediment pollution. Results showed that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the same line, the work performed by Ramírez-Pérez and co-authors [12] investigated the geochemistry, enrichment, and pollution of trace metals in anoxic sediments, pointing to a possible ecotoxicological risk to organisms for Pb, Cu and Zn in superficial sediment layers in the San Simon Bay (Spain), contaminated in the surface mainly due to anthropogenic inputs, especially in the case of Pb, reflecting the enormous human pressure on these ecosystems. Huang and co-authors [13] studied the causes of copper and other common heavy metals input in sediments of irrigation canals in Taiwan province (China). They observed that sediments were polluted mainly due to the highest masses of pollutants released into drainage wastewater of the county and the return flow from irrigation, and the illegal discharge of wastewater.…”
mentioning
confidence: 99%
“…In the same line, the work performed by Ramírez-Pérez and co-authors [12] investigated the geochemistry, enrichment, and pollution of trace metals in anoxic sediments, pointing to a possible ecotoxicological risk to organisms for Pb, Cu and Zn in superficial sediment layers in the San Simon Bay (Spain), contaminated in the surface mainly due to anthropogenic inputs, especially in the case of Pb, reflecting the enormous human pressure on these ecosystems. Huang and co-authors [13] studied the causes of copper and other common heavy metals input in sediments of irrigation canals in Taiwan province (China). They observed that sediments were polluted mainly due to the highest masses of pollutants released into drainage wastewater of the county and the return flow from irrigation, and the illegal discharge of wastewater.…”
mentioning
confidence: 99%